Population Pharmacokinetic Modeling of von Willebrand Factor Activity in von Willebrand Disease Patients after Desmopressin Administration - de Jager, Nico C. B.; Heijdra, Jessica M.; Kieboom, Quincy; Kruip, Marieke J. H. A.; Leebeek, Frank W. G.; Cnossen, Marjon H.; Mathôt, Ron A. A.; for the OPTI-CLOT Group (Thrombosis and Haemostasis, 2020)
Objective Most von Willebrand disease (VWD) patients can be treated with desmopressin during bleeding or surgery. Large interpatient variability is observed in von Willebrand factor (VWF) activity levels after desmopressin administration. The aim of this study was to develop a pharmacokinetic (PK) model to describe, quantify, and explain this variability.Methods Patients with either VWD or low VWF, receiving an intravenous desmopressin test dose of 0.3 µg kg−1, were included. A PK model was derived on the basis of the individual time profiles of VWF activity. Since no VWF was administered, the VWF dose was arbitrarily set to unity. Interpatient variability in bioavailability (F), volume of distribution (V), and clearance (Cl) was estimated.Results The PK model was developed using 951 VWF activity level measurements from 207 patients diagnosed with a VWD type. Median age was 28 years (range: 5–76), median predose VWF activity was 0.37 IU/mL (range: 0.06–1.13), and median VWF activity response at peak level was 0.64 IU/mL (range: 0.04–4.04). The observed PK profiles were best described using a one-compartment model with allometric scaling. While F increased with age, Cl was dependent on VWD type and sex. Inclusion resulted in a drop in interpatient variability in F and Cl of 81.7 to 60.5% and 92.8 to 76.5%, respectively.Conclusion A PK model was developed, describing VWF activity versus time profile after desmopressin administration in patients with VWD or low VWF. Interpatient variability in response was quantified and partially explained. This model is a starting point toward more accurate prediction of desmopressin dosing effects in VWD.
Keywords: desmopressin response; empirical PK; von Willebrand disease